Improving Health Literacy Through the SIGAP DESA Program: Education on Maternal Anemia Prevention and Communicable Disease Control in Bagendit Village - Genialita Fadhilla; Harlena Pratama Putri; Doni Anshar Nuari (Fakultas Kewirausahaan Universitas Garut, 2026)
Limited access to information and health services in rural areas triggers disparities in public health literacy, particularly regarding the risk of maternal anemia and the threat of infectious disease transmission. This community service program, titled